2019
DOI: 10.2147/dddt.s196535
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparisons between ticagrelor and clopidogrel following percutaneous coronary intervention in patients with acute coronary syndrome: a comprehensive meta-analysis</p>

Abstract: Background:The efficacy and safety of ticagrelor following percutaneous coronary intervention for patients with acute coronary syndrome remains unclear. This study sought to evaluate clinical outcomes of ticagrelor as part of dual-antiplatelet treatment for these patients. Methods: PubMed, MEDLINE, Embase, and other Internet sources were searched for eligible citations. The primary end point was major adverse cardiovascular and cerebrovascular events, consisting of cardiovascular death, myocardial infarction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 35 publications
(54 reference statements)
4
26
1
1
Order By: Relevance
“…These metaanalyses got no consensus on the efficacy and safety of ticagrelor treatment. They either mixed all studies together and ignored the heterogeneity between clinical trials and observational studies, or did not perform further subgroup analyses based on other studies (or population) characteristics (13,15,16). In this metaanalysis, we performed prespecified subgroup analyses for MACE and bleeding in RCTs according to PCI strategy, ethnicity, country, and follow-up duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These metaanalyses got no consensus on the efficacy and safety of ticagrelor treatment. They either mixed all studies together and ignored the heterogeneity between clinical trials and observational studies, or did not perform further subgroup analyses based on other studies (or population) characteristics (13,15,16). In this metaanalysis, we performed prespecified subgroup analyses for MACE and bleeding in RCTs according to PCI strategy, ethnicity, country, and follow-up duration.…”
Section: Discussionmentioning
confidence: 99%
“…However, other large clinical trials (8,9) and observational studies (10)(11)(12) drew controversial conclusions. Meanwhile, several metaanalyses published recently also reported inconsistent results (13)(14)(15)(16). Therefore, we conducted a meta-analysis to review previous relevant studies and compared the clinical benefits of ticagrelor and clopidogrel in the ACS population using aspirin to address these conflicting conclusions.…”
Section: Introductionmentioning
confidence: 98%
“…A study conducted by Fan et al . 38 found that clopidogrel was associated with increased risk of major bleeding compared to ticagrelor. On the other hand, Guan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular and hemorrhagic complications are the most common adverse events post PCI treatment, what's more important is that they are also fatal complications in STEMI patients, for instance, the atrial fibrillation, heart failure and stroke caused by intracranial hemorrhage [18][19][20][21][22][23]. In a previous clinical trial, the proportions of deaths, post-infarction angina, re-infarction/ reocclusion and emergency revascularization were 4.48, 15.2, 4.21, and 8.27% in STEMI patients treated by prourokinase during PCI [6].…”
Section: Discussionmentioning
confidence: 99%